Fish Feed Production in Panembangan Village, Banyumas Regency - Dini Siswani Mulia; Juanita Juanita; Cahyono Purbomartono (Altifani Journal: International Journal of Community Engagement, 2023)
Fish feed is the largest component in freshwater fish cultivation. Feed costs reach 60%-70% of total production costs. The availability of sufficient fish food, both in quality and quantity, is one of the key factors in the success of fish farming. Good quality fish feed not only has high protein content, but also has good physical properties, one of which is buoyancy. Mitra is the Mina Mandiri group in Panembangan Village, Cilongok District, Banyumas Regency which has problems in producing quality fish feed. This activity aims to increase the knowledge and skills of partners in making good quality fish food, which has a protein content that suits the fish's needs and has good buoyancy. The method by which activities are carried out includes coordinating the preparation of service activities with partners, socializing activity programs, implementing activities, and evaluating activity results. Partners are quite enthusiastic about this activity. Partners actively discuss and share experiences related to fish feed production and other fish farming issues. The results of the activity show an increase in partners' knowledge and skills in producing quality fish feed by 50%, based on pre & post tests. Service activities will continue to be carried out as a form of concern and transfer of science and technology to the community, as well as the implementation of the tri dharma of higher education.